THE EFFECT OF FINANCIAL DISTRESS, CAPITAL STRUCTURE AND FIRM SIZE ON FIRM VALUE IN THE BANKING SECTOR IN SOUTHEAST ASIA - Budi Santoso; Sulastri Sulastri; Muizzudin Muizzudin; Marlina Widiyanti (SEAN Institute, 2023)
The purpose of this study was to determine the effect of financial distress proxied by Financial Distress Score (FDS), the effect of capital structure proxied by Debt to Equity Ratio (DER) and the effect of firm size proxied by Total Assets (TA) on Firm Value (FV) in the banking sector in Southeast Asia. The number of samples in the study were 82 banks selected through purposive sampling method with the observation period for 2018 to 2022. This research is descriptive statistics with classical assumption tests. The analysis technique used is panel data regression where the common effect model (CEM) is chosen as the best model for this study. The results of the study with the coefficient of determination show that the FDS, DER and TA variables are able to explain changes in firm value by 4.72%. The results of research with the t test show that FDS has no effect on firm value, DER has a significant positive effect on firm value and TA has a significant positive effect on firm value.